Cardiovascular risk factors in school teachers - N. S. Karamnova; A. M. Kalinina; N. V. Oleynikova; R. A. Eganyan; V. A. Vygodin; N. V. Kisseleva (Кардиоваскулярная терапия и профилактика)
Aim. To study the prevalence of cardiovascular risk factors (RFs) in Moscow secondary school teachers. Material and methods. This clinico-preventive examination included 190 teachers from 4 secondary schools in North-Western Moscow Region. The response rate was 94%, the percentage of women was 95,8%, and the mean age of participants was 47,2±0,9 years. All participants underwent anthropometry and the measurement of blood pressure (BP), total cholesterol (TCH), and blood glucose levels. Results. The assessed cardiovascular RFs were absent in 17,6% of the school teachers. The majority of the participants had a combination of various cardiovascular RFs. The prevalence of AH combination with other RFs was 36,2%. The prevalence of AH and newly diagnosed AH was 36,7% and 6,1%, respectively. Antihypertensive therapy (AHT) prevalence was 87,9% in teachers with AH; however, target BP levels were not achieved. The prevalence of smoking and overweight was 28,0%. Normal body weight was registered in 39,3% of teachers, while 32,9%, 24,7% and 3,1% had overweight, obesity and severe obesity, respectively. Abdominal obesity (AO) was observed in 45,3%. Hypercholesterolemia (HCH) prevalence was 48,9%; 53,9% of HCH patients had moderately elevated TCH levels, and 46,1% had substantially elevated TCH concentrations. Overweight, AO, and HCH were more prevalent in teachers with AH: the respective percentages were 86,4%, 67,6%, and 62,1% (p<0,05). Only 36,1% of the teachers had a single RF, while 25,4% and 20,9% had 2 or ≥3 RFs, respectively. Total cardiovascular risk could be categorized in 97,1% of the teachers. High, very high, and intermediate absolute levels of risk were observed in 11,1%, 9,9%, and 39,8%, respectively. The prevalence of low absolute risk and intermediate population risk was 22,2% and 14,1%, respectively. Conclusion. High prevalence of cardiovascular RFs in school teachers justifies active diagnostics and control of these factors. Specific features of RF distribution in this population should be considered while designing and implementing targeted preventive programs.